2016
DOI: 10.18801/jstei.030216.22
|View full text |Cite
|
Sign up to set email alerts
|

Responses of IBA on rooting, biomass production and survival of branch cuttings of Santalum album L., a wild threatened tropical medicinal tree species

Abstract: Clonal propagation is important for the conservation of native, wild and threatening tree species. The study investigates the opportunities of rooting of branch cuttings of Santalum album treated with 0, 0.4, 0.6 and 0.8% indole-3butyric acid (IBA) in a non-mist propagator. A total of four hundreds eighty cuttings were used to assess the rooting ability of this species. The study revealed significant differences (p<0.05) of rooting percent, average root number per cutting and average root length among the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Higher IBA concentrations decreased the rooting percentage in Syzygium cumini [ 65 ]. Another report observed a very high rooting system in Santalum album [ 66 ], Gmelina arborea [ 67 ], and Syzygium malaccense [ 68 ] with and without IBA, indicating that IBA’s influence on root formation during cutting is species-specific and that different plant species require diverse IBA concentrations to induce higher root percentages. The increase in the number of roots per cutting due to IBA treatment found in this study corroborates previous findings [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher IBA concentrations decreased the rooting percentage in Syzygium cumini [ 65 ]. Another report observed a very high rooting system in Santalum album [ 66 ], Gmelina arborea [ 67 ], and Syzygium malaccense [ 68 ] with and without IBA, indicating that IBA’s influence on root formation during cutting is species-specific and that different plant species require diverse IBA concentrations to induce higher root percentages. The increase in the number of roots per cutting due to IBA treatment found in this study corroborates previous findings [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on other species have shown that cuttings from soft wood or juvenile branches are more successful than those from older plant tissue (Azad et al, 2016). The experiment was carried out under non-mist propagation tunnels (Junior et al, 2016;Qadri et al, 2018).The tunnel was made of 4m wide and a 4m long wooden box constructed from round wood measuring 60cm wide by 4cm thick.…”
Section: Methodsmentioning
confidence: 99%
“…Khaya anthotheca, commonly known as East African Mahogany, is a large evergreen tree species native to tropical Africa (Mariano, 2018). Khaya anthotheca is fast growing and grows up to 60 m in height (30 m in gardens) (Azad et al, 2016). The leaves are spirally arranged, alternate, with 3-7 leaflets and darkglossy green in color.…”
Section: Introductionmentioning
confidence: 99%